Probiotic supplementation regulated swine growth performance, fecal odor reduction and carcass characteristics by modulating intestinal microbiome - Yung-Tsung Chen; Yu-Ting Sun; Herng-Fu Lee; Yu-Chun Lin; Ming-Ju Chen (Animal Microbiome)
Abstract Background Using probiotics as a substitute for antibiotic growth promoters and reducing odor has received increasing attention in animal science. Despite the extensive investigation into the effects of probiotic administration on swine growth performance and odor reduction by short study durations, the analysis of carcass characteristics and potential mechanistic insights involving gut microbiota and downstream pathways is still few. Methods A total of 48 crossbred LYD [(Landrace x Yorkshire) x Duroc] piglets (equal numbers of males and females) were randomly assigned to one of four dietary treatments: control (CON), Lactobacillus kefiranofaciens M1 (M1), M1 + Bacillus amyloliquefaciens S20 (SA group) and M1 + S20 + Bacillus subtilis S14 (SAM group). During the nursery phase (4–8 weeks), pigs were pair-housed and monitored for diarrhea. From 8 to 19 weeks of age, pigs were individually housed and fed grower-finisher diets. Growth performance, blood biochemistry, fecal enzyme activity, and odor-related metabolites were assessed at multiple time points. At market weight (~ 110 kg), six pigs per group were slaughtered for carcass and cecal microbiota analysis. Results The results demonstrated that administration of the probiotics led to increased body weight and average daily weight gain, particularly notable during the weaning and finishing periods. Additionally, the SA and SAM groups significantly reduced skatole concentration in feces. Furthermore, probiotic supplementation was associated with increased carcass weight, with the SAM group exhibiting significantly higher tenderloin weight than the CON group. Microbiota analysis revealed taxa exhibiting significant differences in abundance among groups, with corresponding LEfSe findings. Conclusion Administering Bacillus subtilis S14 and B. amyloliquefaciens S20 (SA group) impacted growth performance, reduced fecal odor, and enhanced pig carcass quality. The identified probiotic strains hold promise as feed additives, offering a potential solution to challenges encountered by the swine industry. Graphical abstract